The mediating effect of job satisfaction on leadership styles and organisational commitment among employees from three tourism villages in Indonesia - -, Zulfa Nadia; Tengku Mohd Azzman, Tengku Siti Aisha (University Putra Malaysia, 2017)
A main purpose of this paper is to examine the mediating effects of job satisfaction on leadership style and organizational commitment in tourism villages in Indonesia. This study also focuses on leadership styles in three Indonesian tourism villages: the Poncokusumo tourism village, the Ngadas tourism village and the Gubugklakah tourism village; and how these leadership styles influence job satisfaction and organizational commitment in terms of its implementation. A quantitative research design and a cross-sectional survey are used to test the hypotheses of the study. The sample population of the study consists of managerial staff, guides and homestay employees from the aforementioned tourism villages in Indonesia (N = 152). Findings indicate that there is a relationship between the transformational leadership style and organisational commitment, and a positive significant relationship between transformational leadership style and job satisfaction. Consistent with the prediction, job satisfaction is found to mediate the relationship between leadership style and organizational commitment. It appears that practicing the transformational leadership style and maintaining job satisfaction are important factors in retaining staff commitment to the job as well as to the organization. Implications of this study are especially pertinent to managers in the tourism industry, in terms of being more effective, understanding their employees and being able to create a workplace that avoids internal organizational culturally based conflict. Thus, by comprehending how employees think, managers are able to motivate them, delegate tasks more efficiently and control interactions within the organization.